(untitled) (TAJ: Journal of Teachers Association, 2010)
Adrenocortical carcinoma is an uncommon tumour in the pediatric population. Account for only a small fraction of pediatric adrenal tumour. Most tumors in children are functional, and virilization is by far the most common presenting symptom, followed by Cushing’s syndrome and precocious puberty. All patients with suspected adrenocortical carcinoma should be carefully evaluated for signs and symptoms of hormonal syndromes. DOI: 10.3329/taj.v22i1.5039 TAJ 2009; 22(1): 142-143